Acupuncture in circadian rhythm sleep–wake disorders and its potential neurochemical mechanisms - Wu, Junmei; Zhao, Zhengyu (Frontiers in Neuroscience, 2024)
Circadian rhythm sleep–wake disorders (CRSWDs) are becoming increasingly common in modern societies due to lifestyle changes. The detrimental effects of CRSWDs on sleep and psychological health have attracted considerable attention recently. Alternative remedies for the treatment of CRSWDs have also gained attention in recent years owing to the limitations of medications. Several in vivo and clinical investigations have shown that acupuncture, one of the most important components of traditional Chinese medicine (TCM), has been shown to modulate sleep-related circadian rhythms. Owing to the lack of research on the mechanism and effectiveness of acupuncture in treating CRSWDs, clinical applications of acupuncture have not gained popularity. This paper reviews the acupuncture methods, acupoint selection, and biochemical indicators supplied by in vivo and clinical studies to explore the effectiveness of acupuncture, and summarizes the circadian rhythm mechanisms and the acupuncture characteristics on circadian rhythm. The neurochemical mechanisms linked to acupuncture in treating CRSWDs are also outlined from the perspective of the central and peripheral biological clocks. Lastly, the inadequacy of previous studies on CRSWDs and conflicting results regarding acupuncture are explored and future research directions are envisioned.